2016
DOI: 10.21053/ceo.2015.01508
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Palatal Mucosa Graft in Surgical Treatment of Sub-Glottic Stenosis

Abstract: ObjectivesMucosal free grafts may be successfully applied in many surgical interventions. This study aims at investigating the feasibility of palatal mucosa graft in sub-glottic field in an animal model.MethodsThis randomized prospective controlled study was conducted with an animal model. Sub-glottic inflammation was created in 15 adult rabbits in each group and sub-glottic stenosis surgery was applied thereafter. The rabbits in group 1 (control group) underwent segmental resection, partial cricoidectomy, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…Inflammation at the wound site is an important determinant of wound healing processes. An excessively activated inflammatory response might hinder the regeneration process and eventually lead to hypertrophic scar contraction and fibrosis 37 , 38 . The present study demonstrated that autologous mucosal sheet grafting was well adapted and survived in the surgical wound.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation at the wound site is an important determinant of wound healing processes. An excessively activated inflammatory response might hinder the regeneration process and eventually lead to hypertrophic scar contraction and fibrosis 37 , 38 . The present study demonstrated that autologous mucosal sheet grafting was well adapted and survived in the surgical wound.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory reactions at the wound site are an important determinant of healing. The regeneration potential might be hindered by excessive inflammatory responses that eventually result in fibrosis and hypertrophic scar formation 31 , 32 , as supported by the collagen deposition and the presence of myofibroblasts in control wounds in our study. The pre-vascularized mucosal grafts prevented excessive inflammatory responses and granulation formation in the wounds, eventually facilitating a more natural wound healing process 33 .…”
Section: Discussionsupporting
confidence: 66%
“…Inflammation at wounded sites is an important determinant of the wound healing process. Excessively activated inflammatory responses may hinder the regeneration process and eventually contribute to scar contraction and fibrosis, resulting in remnant scarring and adhesion after wound healing . The present study showed that oral mucosa equivalent grafts adapted well and survived in the bed of repeat major ulcer.…”
Section: Discussionmentioning
confidence: 49%